IMPACT OF E-BANKING SERVICES ON INDIAN SOCIETY - 1. Dr. Vandana Prabhakar Dangle , 2. Asst. Prof. Atish Prakash Waghchaure (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
In this research, the effects of e-banking services on Indian society are analysed commercial banks enhance their offerings through the use of digital technology, which has a favourable impact on their customers, banking operations, and banking procedures through the adoption of digital transformation. In addition, the study analyses consumer behaviour about digital banking and concludes that the banking industry's digital revolution improves bank effectiveness. This study examines how commercial banks constantly make technological advancements to better serve their clients.